Os determinantes do comportamento da dívida pública brasileira na década de 1990 - Nicchio, José Adolfo (2001)
The main goal of this research is to identify the causes of the Brazilian public debt growth in the 90's. Initially it reviews the literature to show the relevant variables that can affect public debt, emphasizing the size of the debt as a proportion of GDP and its cost, the total amount of interests paid on debt. Then, it implements an analysis of the Brazilian economy during the 1980 and 1990 decades. After this analysis, it was possible to identify other important variables to public debt, such as: government credibility, moral hazard, maturity of government bonds, effective interest rate paid, and sustainability of public debt. Hence, the empirical analysis tested the hypothesis of causality of interest differential, between effective interests paid on debt and interest paid on overnight operations, on federal debt in bonds. Moreover, it applied cointegration analysis to the hypothesis of sustainability of Brazilian public debt. The results demonstrate that government has to pay a higher premium to its lenders, and this in turn implies the size of the Brazilian public debt. The direct interpretation recalls the mechanism of financing operational government debts during 1980's and 1990's. Notwithstanding, the co-integration analysis shows that there is sustainability of the Brazilian public debt in the long run, despite of the growing of debt in proportion of GDP in the sort run.